Potencial genético de variedades tradicionais de feijão-caupi para produção de grãos secos e verdes - Freitas, Thaisy Gardênia Gurgel de (Universidade Federal Rural do Semi-Árido, 2015)
Cowpea (Vigna unguiculata) also called deijão-macassar and bean-to-string is one of the main foods of plant origin of the small producer in northeastern Brazil. It is widely cultivated in irrigated areas in the northeast, but is almost always subject to the uncertainties of drought. The objective of this study was to evaluate the genetic potential of traditional varieties for the production of green and dry beans. Two experiments were conducted, in which we evaluated 12 traditional varieties purchased from municipalities of Rio Grande do Norte. We used the design of randomized blocks with five replications. The cultivars were grown in plots formed by four rows. One of the rows of floor area was used to evaluate the yield of green grains, number of pods per plant, number of seeds per pod, weight of hundred grains, length, width and thickness of green pods and length, width and thickness of green beans . The other row to assess the yield of dried beans, dried number of pods per plant, number of grains per pod dried, hundredfold mass, length, width and thickness of dried beans. Held joint analysis of both experiments and correlation between the characters studied. The varieties presented high growth performance and high genetic potential to be used directly by farmers or used in breeding programs for selection of desirable characteristics
Genetic potential of traditional variety cowpea for dry and green beans production
Keywords: Vigna unguiculata; Cultivares tradicionais; Correlação; Feijão de corda; Vigna unguiculata; Traditional cultivars; Correlation; Cowpea; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA